Comparison of Double Intravenous Vasopressor Automated System Using Nexfin Versus Manual Vasopressor Bolus Administration for Maintenance of Hemodynamic Stability During Spinal Anesthesia for Cesarean Delivery: A Randomized Double-blind Controlled Trial. Issue 1 (March 2019) - Sng, B.L.; Du, W.; Lee, M.X.; Ithnin, F.; Mathur, D.; Leong, W.L.; Sultana, R.; Han, N.R.; Sia, A.T.H.
Abstract : ( Eur J Anaesthesiol . 2018;35:390–397) Maternal hypotension is common when spinal anesthesia is administered for cesarean delivery. This can lead to maternal and fetal adverse effects. In an attempt to prevent maternal hypotension, various strategies have been used, such as intravenous fluid boluses and administration of intravenous vasopressors. None of these techniques, however, have been able to eliminate spinal-induced hypotension. Vasopressors (phenylephrine or ephedrine) are some of the most common strategies for the prevention of maternal hypotension. Because of the frequent fluctuations of blood pressure (BP) that occur during spinal anesthesia, though, it has been difficult to determine the optimal timing and dosing of vasopressors during cesarean delivery.